Table of Content - - (Journal of medical and pharmaceutical sciences, 2025)
Table of Content: • The Role of Patient Complaint Handling in Improving Healthcare Quality: A Field Study at Jazan General Hospital - Kingdom of Saudi Arabia 2025 Dr. Hamad Mohammed Mania, Mrs. Mona Ali Daraaj • Epidemiological Analysis of Diphtheria Cases in Hodeida, Yemen: A Review of Admission Records from 2018 to 2022 Dr. Najeeb M.S. Moulhee, Dr. Sadeq Abdo Mohammed Alwesabi ,Dr. Mogeeb Saeed Taha , Dr. Ahmed Suliman Mohamed Majam • Comparative Study of Psoriasis and Atopic Dermatitis Asst- Lecturer / Fatima Rashid Mohan • Ultrasound-Detected Metabolic Dysfunction-Associated Steatotic Hepatopathy (MASH) Prevalence in Type 2 Diabetes Patients Attending Primary Care Muammar Basheer Yasir, Dr. Al-Mottesembellah Abdalruhman Gaiz, Noor Abdulredha Jaleel • Cancer Burden in the Red Sea State, Sudan: A Ten Years of Incidence, Distribution, and Trends: (2016 - June 2025) Dr. Awad Abdalla Widaa